2022
DOI: 10.2337/dc22-0833
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin G N-Glycosylation Signatures in Incident Type 2 Diabetes and Cardiovascular Disease

Abstract: OBJECTIVE N-glycosylation is a functional posttranslational modification of immunoglobulins (Igs). We hypothesized that specific IgG N-glycans are associated with incident type 2 diabetes and cardiovascular disease (CVD). RESEARCH DESIGN AND METHODS We performed case-cohort studies within the population-based European Prospective Investigation into Cancer and Nutrition (EPIC)–Potsdam cohort (2,127 in the type 2 diabetes subco… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…In addition, a study of Chinese Muslim ethnicity and the Han population reported associations of IgG-glycans with hypertension and type 2 diabetes mellitus comorbidity [ 45 ]. A study of European samples developed a score based on significant IgG-GPs, which was associated with higher diabetes risk and was robust against confounder and clinical biomarkers [ 46 ]. Similarly, using the 2617 participants of the TwinsUK cohort, the glycan score of hypertension was built and indicated that the IgG glycome changes prior to the development of hypertension [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a study of Chinese Muslim ethnicity and the Han population reported associations of IgG-glycans with hypertension and type 2 diabetes mellitus comorbidity [ 45 ]. A study of European samples developed a score based on significant IgG-GPs, which was associated with higher diabetes risk and was robust against confounder and clinical biomarkers [ 46 ]. Similarly, using the 2617 participants of the TwinsUK cohort, the glycan score of hypertension was built and indicated that the IgG glycome changes prior to the development of hypertension [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most unique change was the decrease in the bisecting structures, stemming mainly from the decrease in the FA2B and FA2[6]BG1. An increased bisecting is noticed throughout the literature, in studies looking at the IgG N -glycosylation in inflammation, diabetes, CVD, and hypertension, which are all states that are associated with AF [ 24 , 27 , 28 ]. Furthermore, higher levels of bisecting N-acetlyglucosamine have been associated with proinflammatory IgG changes due to an increased binding to FcγRIII, and consequently, an increased antibody-dependent cellular cytotoxicity (ADCC) [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, higher levels of bisecting N-acetlyglucosamine have been associated with proinflammatory IgG changes due to an increased binding to FcγRIII, and consequently, an increased antibody-dependent cellular cytotoxicity (ADCC) [ 44 ]. The changes in FA2[3]G1 are also of the opposite direction compared to those that are noticed in diabetes and CVD [ 24 , 28 , 29 ]. Overall, an inflammatory IgG profile, present in these conditions and consisting of decreased galactosylation and sialylation, is not reveled in AF.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations